2022
DOI: 10.3390/ma15238333
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Selective Absorption of Molybdenum Nanostructured Surfaces for Concentrated Solar Energy Applications

Abstract: Surfaces of commercial molybdenum (Mo) plates have been textured by fs-laser treatments with the aim to form low-cost and efficient solar absorbers and substrates for thermionic cathodes in Concentrated Solar Power conversion devices. Morphological (SEM and AFM), optical (spectrophotometry), and structural (Raman spectroscopy) properties of the samples treated at different laser fluences (from 1.8 to 14 J/cm2) have been characterized after the laser treatments and also following long thermal annealing for simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It should be noted that, upon ablation in air, an oxide layer can be formed on the top of the ablated metal. However, according to Santagata et al [ 3 ], this effect becomes important for molybdenum at fluences above 10 J/cm , which is much higher than applied in our experiments. Indeed, Raman analysis shows only some traces of MoO (not presented here).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…It should be noted that, upon ablation in air, an oxide layer can be formed on the top of the ablated metal. However, according to Santagata et al [ 3 ], this effect becomes important for molybdenum at fluences above 10 J/cm , which is much higher than applied in our experiments. Indeed, Raman analysis shows only some traces of MoO (not presented here).…”
Section: Resultsmentioning
confidence: 57%
“…In recent years, the fabrication of highly regular laser-induced periodic surface structures (HR-LIPSSs) over large areas using ultrashort laser pulses has been a topic of interest due to their scientific and industrial applications [ 1 , 2 , 3 ]. Self-replication of the LIPSS makes it possible to cover material surfaces with ripples by scanning the laser beam with appropriate parameters [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that the LIPSS−Mo surface pair can improve the solar spectral selectivity by a maximum of about 4 times. 28 With the significant performance improvements on solar absorptance and selectivity as well as the high thermal and mechanical stability, the LIPSS−Mo surface pair is the most promising candidate for low-cost, efficient, and high-temperature selective solar absorbers in concentrated solar energy devices. Besides, the LIPSS−Mo surface pair enables other numerous potential applications in antifriction, antibacteria, biocompatibility, superhydrophobicity, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The dual-color correlated laser nanostructuring not only provides a strategy for manufacturing structures on metals with 100 nm feature sizes but also renders new functions by altering its properties in optics, mechanics, chemistry, and biology. The nanostructured Mo surface not only displays performance improvements on solar absorptance and selectivity, which are beneficial for efficient solar absorber applications, , but also enables other potential applications in antifriction, antibacteria, biocompatibility, superhydrophobicity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known, in fact, that mechanical strains can alter the electronic, optical, and mechanical properties of 2D crystals [ 9 ] and that “elastic strain engineering” is becoming a useful tool for bulk materials as well [ 10 ]. On the other hand, chemical modifications can be laser-induced (e.g., superficial oxidation [ 11 ]), or new chemical functional groups can be introduced post-irradiation via surface adsorption [ 12 ]. In this context, characterization by Raman spectroscopy is useful for assessing possible chemical modifications.…”
Section: Introductionmentioning
confidence: 99%